Corner of Dock and Faneuil Hall Squares, ca. 1900 - Halliday Historic Photograph Co. (Tufts Archival Research Center, 2005)
Street-level view southwest of the southwest corner of Faneuil Hall and Dock Squares. Awnings and signage adorn the facades of the buildings included in the photograph. The facades of those buildings visible in the left half of the photograph face northeast towards Faneuil Hall Square, while the facades of those buildings visible in the right half of the photograph face north-northwest towards Dock Square. A street light is located at the corner of Faneuil Hall and Dock Squares. The northeast corner of the Ames Building, located at the northwest corner of Court and Washington Streets, is visible in the background, near the upper-right corner of the photograph. 6 1/4 x 7 7/8 Photographs